2023
DOI: 10.1111/jgs.18226
|View full text |Cite
|
Sign up to set email alerts
|

Worth it if you could afford it”: Patient perspectives on integrating real‐time benefit tools into drug cost conversations

Abstract: Background Medication costs can lead to financial burdens for patients, creating barriers to effective medication use. Health care provider use of real‐time benefit tools (RTBTs) may facilitate cost conversations with patients. We sought to explicate patient views on how RTBTs could be used to improve cost considerations in prescribing decisions. Methods We conducted focus groups to characterize patient perspectives on holding cost conversations with their physicians and to identify factors that would influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The authors conducted qualitative interviews with a diverse group of patients to evaluate their views of cost‐of‐care conversations and the role that RTBTs might play in facilitating them. The findings from this article, as well as the same group's previously published article on clinicians' perspectives of RTBTs, 4,15 suggest that several important actions should be taken to ensure that RTBT use is practical and helps improve patient care, especially for complex patients like Ms. Smith.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…The authors conducted qualitative interviews with a diverse group of patients to evaluate their views of cost‐of‐care conversations and the role that RTBTs might play in facilitating them. The findings from this article, as well as the same group's previously published article on clinicians' perspectives of RTBTs, 4,15 suggest that several important actions should be taken to ensure that RTBT use is practical and helps improve patient care, especially for complex patients like Ms. Smith.…”
mentioning
confidence: 81%
“…Both patients and clinicians worry that RTBT use will prolong clinical encounters and/or take time away from other important clinical matters. 4,15 Prior analyses of audio-recorded encounters have found that cost-of-care conversations typically last only 1 or 2 min, 17 but these analyses were conducted prior to the existence of RTBTs. Now that real-time cost information is available, cost-ofcare conversations may take longer and be more nuanced as clinicians and patients discuss the tradeoffs of various medications with varying cost, efficacy, and side effect profiles.…”
Section: Clinicians Should Have Additional Time For Cost-of-care Conv...mentioning
confidence: 99%
See 3 more Smart Citations